Game-Based Learning to enhance Speaking Skills (2023)
ABSTRACT: This action research project investigates the implementation of game-based learning to enhance speaking skills in a group of English intermediate level students. It aims to actively implement and observe the effects of game-based learning in the classroom. The study hypothesizes that incorporating games into language instruction can effectively engage students, encouraging them to participate in communicative activities and ultimately improving their speaking abilities. By creating an enjoyable and motivating environment, games offer students authentic opportunities for communication, collaboration, and feedback. The findings of this study will contribute to the understanding of the benefits of game-based learning in language education.